HUBUNGAN SELF EFIKASI DENGAN TINGKAT RESILIENSI DAN KUALITAS HIDUP MASYARAKAT DALAM MENGHADAPI BENCANA BANJIR DI KELURAHAN TRIMULYO (Nursing Care Journal, 2023)
The flood disaster brings various negative impacts on the community, such as post-disaster trauma, losing tranquility, and increased stress due to the disaster. The impacted community due to flood includes decreased resilience and life quality due to the disaster. Then, the decreased condition requires self-perception of the community to improve resilience and life quality. This research analyzed the correlation between self-efficacy toward resilience and life quality improvement of the community to deal with a flood. This research used non-probability sampling. The sample was taken with purposive sampling, resulting in 51 respondents. The researchers took the data with the questionnaires on self-efficacy, resilience, and World Health Organization Quality of Life Brief Version, WHOQoL-BREF. The researcher used the Gamma Correlation test and obtained a p-value of 0.011, lower than 0.05. The result indicated the significant correlation between self-efficacy and resilience of the community in Trimulya administrative village, Semarang. The obtained correlation coefficient was 0.817. The score indicated a positive correlation. Thus, higher self-efficacy led to higher resilience of the community people strongly. The Gamma Correlation test for self-efficacy and life quality obtained a p-value of 0.003, lower than 0.05. The result indicated a significant correlation between self-efficacy and the life quality of the community in Trimulya administrative village, Semarang. The obtained correlation coefficient was 0.807. The score indicated a positive correlation. Thus, higher self-efficacy led to the higher life quality of for the community people strongly. The results recommend further researchers use more relevant resources and references related to self-efficacy, resilience, and life quality.